Prevalence and Transmission of Fusarium moniliforme: A Seed Borne Pathogen of Rice (Bangladesh Rice Journal, 2021)
Fusarium moniliforme is one of the major seed borne pathogen of rice in Bangladesh that causes significant yield loss. To observe the incidence and transmission of this pathogen, farmers saved seeds and seeds from BADC were collected and the pathogens were detected by blotter method. The prevalence of the F. moniliforme varied according to locations and seasons. The highest 18% of seed infection was recorded in Boro seeds of Netrakona district and the lowest 2% was in Gazipur district. The Embryonal end of the seed is the most preferable site of the infection. F. moniliofrme successfully transmitted from seed to seedling and the transmission is high when pre- sprouted seed sown on the puddled seed bed. The study recommended that before planting season, seeds should be tested and treated when necessary to minimize spread of the pathogen.Bangladesh Rice J. 24 (1): 11-19, 2020